2011
DOI: 10.1080/1065657x.2011.10736971
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Manure Windrow Composting Runoff And Infiltration Characteristics from Laboratory Rainfall Simulations

Abstract: Windrow-composted livestock manure has been shown to be less hazardous to the environment compared to manure directly applied to cropland and other agricultural areas. Although offsite contaminant losses through runoff and leaching can occur during the composting process, these losses are suspected to increase under different compost moisture conditions and as composted materials mature. This research quantified the effects of windrow-composted livestock manure and straw bedding components on runoff and infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…However, when extended to 24 h from the onset of rain simulation, VRC increased to 0.53 to 0.84, which corresponded to our values during mid‐ to late active composting. Webber et al (2011) reported a VRC of 0.25 on Day 0 for manure/straw in a compost windrow cross‐section container apparatus, which was very similar to our initial value of 0.24 for a similar feedstock. Their VRC increased to 0.39 for Day 30 compost, which, although lower than our estimate of 0.49 for Day 30, supported the trend of increased VRC with increased maturity.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, when extended to 24 h from the onset of rain simulation, VRC increased to 0.53 to 0.84, which corresponded to our values during mid‐ to late active composting. Webber et al (2011) reported a VRC of 0.25 on Day 0 for manure/straw in a compost windrow cross‐section container apparatus, which was very similar to our initial value of 0.24 for a similar feedstock. Their VRC increased to 0.39 for Day 30 compost, which, although lower than our estimate of 0.49 for Day 30, supported the trend of increased VRC with increased maturity.…”
Section: Resultssupporting
confidence: 85%
“…In fact, the highest runoff rates and VRCs occurred with lower AWC (Days 81 and 109). Webber et al (2011) found no significant difference in VRC between unsaturated and saturated composts. During the humification of organic matter as compost matures, carbohydrates (hydrophilic‐C) decrease, whereas alkyl‐ and aromatic‐C (hydrophobic‐C) compounds increase (Aguiar et al, 2013; Spaccini and Piccolo, 2009).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Studies have documented nutrient losses, either through leaching or runoff, from a wide range of compost feedstock mixtures, including: animal manures (Eghball et al 1997;Glanville et al 2006;King et al 2009King et al , 2014Martins and Dewes 1992;Seymour and Bourdon 2003;Ulen 1993;Webber et al 2011), food waste (Krogmann and Woyczechowski 2000), and yard waste (Ballestero and Douglas 1996). There is not a universal agreement on the relative importance of these mechanisms, however.…”
Section: Introductionmentioning
confidence: 92%
“…Treatments used to reduce microbial concentrations in manure, such as composting and digesting, could affect microbial release as well. Webber et al (2011) performed a windrow composting study and conducted rainfall simulations over composted manure (mixture of straw bedding, dairy cow waste, horse waste, and sheep waste) on Days 0, 30, and 60 of composting and measured NO 3 -N, PO 4 -P, and sediment losses in runoff and leachate. The authors reported significantly lower leachate volumes and higher runoff volumes of all contaminants as the composting time increased, which was attributed to changes in manure bulk density, aggregation, porosity, and water contents (i.e., physical contents related to manure consistency).…”
Section: Manure Treatment Effectmentioning
confidence: 99%